Assessment of wastewater and recycled water quality: A comparison of lines of evidence from in vitro, in vivo and chemical analyses - Leusch, F.; Khan, S.; Gagnon, Marthe Monique; Quayle, P.; Trinh, T.; Coleman, H.; Rawson, Christopher; Chapman, H.; Blair, P.; Nice, H.; Reitsema, Tarren (IWA Publishing, 2014)
We investigated water quality at an advanced water reclamation plant and three conventional wastewater treatment plants using an “ecotoxicity toolbox” consisting of three complementary analyses (chemical analysis, in vitro bioanalysis and in situ biological monitoring), with a focus on endocrine disruption. The in vitro bioassays were chosen to provide an appropriately wide coverage of biological effects relevant to managed aquifer recharge and environmental discharge of treated wastewater, and included bioassays for bacterial toxicity (Microtox), genotoxicity (umuC), photosynthesis inhibition (Max-I-PAM) and endocrine effects (E-SCREEN and AR-CALUX). Chemical analysis of hormones and pesticides using LCMSMS was performed in parallel to correlate standard analytical methods with the in vitro assessment. For two plants with surface water discharge into open drains, further field work was carried out to examine in situ effects using mosquitofish (Gambusia holbrooki) as a bioindicator species for possible endocrine effects.The results show considerable cytotoxicity, phytotoxicity, estrogenicity and androgenicity in raw sewage, all of which were significantly reduced by conventional wastewater treatment. No biological response was detected to RO water, suggesting that reverse osmosis is a significant barrier to biologically active compounds. Chemical analysis and in situ monitoring revealed trends consistent with the in vitro results: chemical analysis confirmed the removal trends observed by the bioanalytical tools, and in situ sampling did not reveal any evidence of endocrine disruption specifically due to discharge of treated wastewater (although other sources may be present). Biomarkers of exposure (in vitro) and effect (in vivo or in situ) are complementary and together provide information with a high level of ecological relevance. This study illustrates the utility of combining multiple lines of evidence in the assessment of water quality.